Entry and Exit of Banks in Latin America and the Caribbean: Public Policy Concerns and a Proposed Solution - George J. Benston (Inter-American Development Bank, Office of the Chief Economist, 1997)
Banking authorities must resolve or otherwise deal with existing banks that are weak or insolvent without imposing costs on consumers or taxpayers. Two aspects of this concern should be delineated. First, how can banking regulations be structured so that the future exit of weak and insolvent banks would be relatively costless? Next, how can the authorities resolve existing weak and insolvent banks without imposing costs on depositors or taxpayers?
Keywords: 330; Bankenregulierung; Markteintritt; Wettbewerb; Einlagensicherung; Lateinamerika; Marktaustritt